USUARIO2739GO USUARIO2739GO Matemática Respondido a) (3)^3 x (-2)^2 + (3)+ 5^0 = b)(-1)3+3+(+2).(+5)= c)(-2) x (-7) + (3) ^2= d)2 x (5)^2 -3 - (1)^3 +4= e) - [ -1+(-3) x (-2] ^2= f) - (5-7)^3-[ 5-2^2 - ( 4 - 6 ) ] = g) ( -3 + 2 - 1 )^3 - ( -3 + 5 - 1)^8 + 3 = h) 8-[-7+)-1) x (-6) + 4 ] ^2= i)14-[(-1)^3 x (-2)^2 + (-35): (+5)]= j) 5^3 - [ 10 + (7-8)^2] -4 + 2^3= k)(-1)^8 + 6^0 - [ 15 + (-40) : (-2)^3]= l) - 3 - [ - 2 -[ (-35) : (+5)+ 2^2 ] = m) 5-[ + 3 - [ (2)^2 - ( -5)^2 + 6 - 4 ]-3= n)15-[-3+[ (5 - 6)^2 x ( 9-8)^2 + 1]= o) 18-[ 6 - [ -3 - (5-4) - (7-9)^3] - 1 ]= p) - 2 + [ -5 - [ - 2 - (- 2) ^3 - 3 -(3-2) ^9 ] + 5 ] q) 4 - [ (-2)^2 x ( -3) - [ - 11 + (-3) x (-4)] - (1) ] =